STRATEGI PENGELOLAAN EKOWISATA PADA MASA NEW NORMAL DI KEBUN RAYA CIBODAS - Anugrah Putra Syafithra; Messalina L Salampessy; Kustin Bintani Meiganati; Winarni Winarni (Jurnal Belantara, 2022)
The COVID-19 pandemic has impacted various fields, especially the tourism sector in Indonesia. Cibodas Botanical Gardens (KRC) as an ecotourism destination as well as a conservation area that has an important role in the welfare of the surrounding community and the environment, requires appropriate management strategies in the new normal. The purpose of this study is to determine the development of ecotourism strategies during the new normal period in KRC. Data was collected using survey methods and literature studies, survey methods were carried out by direct observation, documentation and interviews. Interviews were conducted with managers, communities and visitors, with 30 respondents each. Determination of the sample is done by purposive sampling method. Literature studies are carried out by obtaining data through books and scientific journals as well as related agencies websites. Data analysis used SWOT (Strength, Weakness, Opportunities, Threats) analysis. The results showed that the total score for the Internal Factor Evaluation was 0.57722 and the total score for the External Factor Evaluation was 0.58789 with a quadrant I (one) position, namely Aggressive, with a strategy of mitigating COVID-19 alert in ecotourism services, coaching and community assistance, make policies and special services for COVID-19, create new innovation programs and infrastructure, build cooperation in the fields of service, tourism business, and environmental security as well as form environmentally conscious and conservation organizations.